Impact of Phosphorus on Water Quality - Rao Mylavarapu (EDIS, 2009)
SL-275, a 4-page fact sheet by Rao Mylavarapu, highlights the role of phosphorus, interactions with the environment, and its potential impact on water quality. It is intended to serve audiences such as high school students, farmers, and the general public seeking information on the causes and mechanisms of potential phosphorus effects on water quality. Includes references. Published by the UF Department of Soil and Water Sciences, December 2008.